IMAGERY IN THE POETRY COLLECTION ANNO 2020 BY ALOIS A. NUGROHO: CITRAAN PADA KUMPULAN SAJAK ANNO 2020 KARYA ALOIS A. NUGROHO - Adelia Putri; Imam Safi’i (Jurnal Kata, 2024)
Poetry is modern poetry created through the thoughts, experiences, and feelings of the poet arranged in beautiful words. The purpose of this research is to describe the visual imagery, auditory imagery, motion imagery, tactile imagery, and olfactory imagery in the poems of Anno 2020. This research uses a qualitative descriptive approach. This research produces 18 data, including 7 visual imagery data, 3 auditory imagery data, 3 motion imagery data, 5 sensory imagery data, and 0 olfactory imagery data. The most dominant imagery is visual imagery and the least imagery is auditory imagery.